The Dynamic Expression of Potential Mediators of Severe Acute Respiratory Syndrome Coronavirus 2 Cellular Entry in Fetal, Neonatal, and Adult Rhesus Monkeys - Cao, Bangrong; Zhang, Liping; Liu, Huifen; Ma, Shiqi; Mi, Kun (Frontiers in Genetics, 2021)
The COVID-19 pandemic, induced by the pathogenic SARS-CoV-2 has spread rapidly all over the world. There is considerable variability among neonates, children and adults in the incidence of infection and severe disease following exposure to SARS-CoV-2. In our study, we analyzed the trancriptome data of primate animal model of Rhesus monkeys to evaluate the expression levels of possible SARS-CoV-2 receptors and proteases and immunologic features in the lungs, colons, livers and brains at different developmental stages. Our results revealed ACE2 and TMPRSS2 were highly expressed in neonates compared to other populations which imply the high incidence of infection. Other potential receptors and Type II transmembrane serine proteases and cathepsin of endosomal proteases also exhibited dynamic and differential expression patterns. The expression of receptors (ACE2, BSG, DPP4) and proteases (TMPRSS2, TMPRSS9, CTSL, CTSB) were highly correlated during lung development, suggesting the high susceptibility of lungs. TMPRSS9 was specifically high expressed in lungs and reached the highest level in neonates similar to TMPRSS2. Moreover, the immune cell infiltration analysis revealed immunity immaturity in neonates implying the association with the mild or moderate type of COVID-19. The results might help researchers design protective and therapeutic strategies for COVID-19 in populations at different ages.